The Influence of Service Quality, Price, Promotion and Electronic Word of Mouth (E-Wom) on Purchasing Decisions on Shopee E-Commerce - Akbar, Mochammad; Rachmawati, Erny; Purwidianti, Wida; Miftahuddin, Muchammad Agung (Asian Journal of Management Analytics, 2025)
This study aims to analyze the influence of service quality, price, promotion, and electronic word of mouth (e-WOM) on purchase decisions on the Shopee e-commerce platform. A quantitative approach was used by collecting data through questionnaires to 130 students in Purwokerto who had shopped through Shopee in the January-May 2025 period. Data is analyzed using the SmartPLS application 3. The results showed that promotion and e-WOM had a significant positive effect on purchase decisions, while service quality and price did not show a significant influence. These findings confirm the importance of digital promotions and user-generated content in influencing online consumer behavior and providing strategic input for the development  of e-commerce marketing.